ANALISIS PENGARUH PROMOSI TERHADAP PENINGKATAN PENJUALAN JASA PADA PT. PRUDENTIAL LIFE ASSURANCE KABANJAHE - Menanti Sembiring; Benni Purba (JURNAL REGIONOMIC, 2019)
This research is aim to investigate the influence of promotion towards the increasing of sale service in PT. Prudential Life Assurance, Kabanjahe. Population of this research is about 724 of people and to be taken about 88 of people to become sample. Technique of collecting data which is used is by questioner that by doing sharing questioner to respondent. Technique of analyzing data which is used is Simple Linier Regression, and also for investigating the contribution of promotion’s variable towards the increasing of sales, there will be used determination coefficient formula (R2 ). After analyzing the data, we will get regression formula Y = 5,678 + 0,805X + e automatically. Then, we will get the value of determination coefficient (R2 ) about 0,606 which mean that the promotion that has been done by PT. Prudential Life Assurance was able to influence the increasing of assurance sale service about 60,60 % and its rest about 39,40 % was influenced by the other factor. For testing hypothesis in this research, used test t and gotten the value of tcalculated = 11,513, and t table = 1,662. So, by this investigation can be known that promotion is able to influence the increasing of sale significantly in PT. Prudential Life Assurance, Kabanjahe.